A IMPLEMENTAÇÃO DAS POLÍTICAS PÚBLICAS TERRITORIAIS NA PERSPECTIVA DE ARRANJOS PRODUTIVOS LOCAIS: UM ENFOQUE MEDIANTE A COMPLEXIDADE DO APL DE TRICOT DE IMBITUVA-PR. - Bobato, Zaqueu Luiz (2012)
This study search to understand how the model of production organization in Brazil called the Local Productive Arrangement (APL) has entered the national territory, consequently being disseminated to many regions and parts of the country through the perspective of promoting development processes. Amid the general understanding of the proposal for APL, this study is directed to a comprehensive approach to the case of knitting APL existing in the town of Imbituva, Paraná State,aimed at discussing the public policy of regional and local development proposal from the perspective of APL’s models amid the process of political decentralization in Brazil. The study also aimed to identify the fundamental elements of formation process of knitting companies concentration in Imbituva-PR, as well as understand how the local development project of the knitting APL was put in practice in Imbituva territory, and how this is inserts in the economic-territorial dynamic town of Imbituva. The search also seeks to understand the cooperation, participation and governance relations of the agents who belong to knitting APL. Within a geographical perspective it is a discussion around concepts such as region, territory, globalization, local and territorial development, political decentralization, participation and governance, cooperation, and others. The discussions intend to converge to the object of the present study. In this, are witnessed complex relations about the project with public policy character implemented by the State of Paraná linked to the Brazilian Service to Support Micro and Small Enterprises (SEBRAE). It is seen that part of the local business community did not understand what actually is the project established since the year 2005, and consolidated in 2006 in the territory. The relations of cooperation, participation and governance in arrangement occur so fragmented, leading to losses for the territorial collective, however, notes that there are processes of cultural nature rooted in the city, and these are not being taken into consideration by the project established. The problems perceived in APL focused, allow to conclude that it is necessary to rethink the way it operates in the territory, in order to that its development occurs satisfactorily. Therefore, it is ‘sine qua non’ condition the commitment and involvement of business owners with the public sphere in various scales of Brazilian politics.